Uganda : Technical Assistance Report-Enhancing the Performance of Public Investment Management. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses recommendations for enhancing the performance of public investment management in Uganda. The current public investment program (PIP) is overextended and a stock-take is required (by September 2017) as the basis for further decisions. Cabinet endorsement of important decisions on the PIP is needed to provide a framework for subsequent planning, budgeting and decision making by the Ministry of Finance, Planning and Economic Development (MoFPED), the National Planning Authority (NPA), and Ministries, Departments, and Agencies. To inform the Cabinet decision on the PIP, a comprehensive review of the PIP should be conducted each September/October jointly between the MoFPED, the NPA and the sectors concerned under the auspices of the Development Committee.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet